Securities Data Company and Zephyr, data sources for M&A research - Bollaert, Helen; Delanghe, Marieke (Journal of Corporate Finance, 2015)
We carry out an in-depth analysis of two mergers and acquisitions (M&A) databases: Securities Data Company M&A (SDC) by Thomson Reuters and Zephyr by Bureau Van Dijk (BvD). Our aim is to assess the quality of their information and their suitability for different types of research questions. Our results suggest that overall, SDC has the edge due to two key shortcomings in Zephyr: the continuous overwriting of firm-level data and inaccuracies in announcement dates. However, our analyses also reveal some weaknesses in SDC and show that for some specific research questions, notably relating to the vendor or to acquisitions involving multiple acquirers and targets, Zephyr seems more suitable than SDC.